A78 Establishing the foundation for Age- and Disability-friendly Road Safety Policies in Sri Lanka. Issue 2 (June 2015) - Ameratunga, Shanthi; Tennakoon, Varuni; Peiris-John, Roshini; Bandara, Saman; Attanayaka, Lasanthi; Attanayaka, Senarath; Wickremasinghe, Rajitha
Abstract: Background: With increased motorization and hazards embedded in the built environment, elderly and people living with physical, sensory and mobility impairments encounter a variety of barriers in transportation, mobility and social participation. The Moneragala district in the Uva province of Sri Lanka provides an opportunistic study base in which to evaluate the context and inherent risks involved through linkage to an existing initiative developing an age- and disability-friendly community. The objective of the study was to identify risks relating to road traffic injury among older people and those living with disability and guide advocacy, community development, and policy change to address these risks in the Uva province in Sri Lanka. Methods: This was a mixed methods participatory research study conducted in three randomly selected divisional secretariats in Moneragala district. The sources of data were collected included a household travel survey of the vulnerable road users of interest (i.e., older people aged 60 years and older, and people living with disabilities aged five year and older), focus groups, key informant interviews and photographic documentation of barriers and facilitators for road safety. Records of road traffic "accidents" (as defined in Police databases) for the past ten years were examined. Areas in the community deemed vulnerable were mapped and photographed. Results: Barriers for travel identified by the vulnerable road users in this study included problems with public transport (inconvenient stops, high foot boards, delays), poor accessibility to roads and important institutions (e.g., hospitals, banks), economical and medical reasons and poor recognition or indifferent attitude of service providers and the public. Common hazards expected to influence injury risks included the state of the pavements or sidewalks (e.g., absent or poorly maintained, too narrow, obstructed by sign posts, light posts or parked vehicles), high speeds of vehicles, the state of the main roads (inadequate signage for crossings, bus stops; lack of tactile paving or other features assisting the visually impaired) and poorly constructed or absent culverts on all types of roads. Suggestions to reduce road traffic injury risks from both the participants and the stakeholders included the introduction of disable-friendly cost effective modes of transportation, improved road engineering designs and transportation infrastructure, public awareness programs for targeted groups (e.g., drivers of public buses and three wheelers, school children and teachers, policy makers and other stakeholders) and the implementation and monitoring of effective legislation. Conclusions: This research highlights both the imperative and substantial potential for identifying and addressing priority needs among the most vulnerable populations as transportation and urban design plans are rolled-out in less-resourced settings.